There was a time for everything : a memoir - Friedland, Judith, 1939- (University of Toronto Press, 2023)
"After the death of her mother when she had just turned ten, Judith Friedland learned to be resilient and to persevere. She met the expectations for upper-middle-class women in Toronto in the 1940s and 50s, which included post-secondary education, marriage, and motherhood. While raising a family and supporting her husband's academic career, she continued her formal education through part-time study and gradually began a journey tailored to herself as an individual. In her 40s, she embarked on her own academic career, rising through the ranks to a tenured full professor and chairing the department of occupational therapy in the Faculty of Medicine at the University of Toronto. In A Time for Everything, Friedland reflects on her life and the fact that over time she has managed to "have it all"--just not all at once. This memoir draws on conversations with family members, friends, work colleagues, and former classmates. It includes family histories that reflect her Jewish life, and it considers feminist issues within academic and health care settings. Personal photos illustrate and augment her life story throughout the text. A Time for Everything tells a story about the expectations many women faced in the mid-twentieth century, the evolution of relationships, and opportunities for living a full life."--